AB0136 THE SUSTAINED POSITIVITY FOR ANTI-DSDNA ANTIBODIES FOSTERS THE ESTABLISHMENT OF AN ATHEROTHROMBOTIC STATUS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (13th June 2020) - Patiño-Trives, A. M.; Aguirre, M. A.; Pérez Sánchez, C.; Laura, P. S.; Luque-Tévar, M.; Arias de la Rosa, I.; Ortega Castro, R.; Abalos-Aguilera, M. D. C.; Espinosa, M.; Seguí Azpilcueta, P.; Pers, J. O.; Barbarroja Puerto, N.; et al.
Abstract : Background: Objectives: 1. This study, developed within the Innovative Medicines Initiative Joint Undertaking project PRECISESADS framework, aimed to identify specific molecular profiles involved in the enhanced CV-risk present in SLE patients and to analyze the relevance of the sustained positivity for anti-dsDNA on the establishment of their atherothrombotic status. Methods: One hundred and twenty-four SLE consecutive patients (not including patients with associated antiphospholipid syndrome), belonging to the PRECISESADS project, were evaluated for the presence of CVD and its association with positivity for anti-dsDNA antibodies. A second cohort of 62 SLE patients was included, of which endothelial dysfunction, lipid profile, the presence of atheroma plaques (identified by a pathologic increase in the carotid intimae media thickness -CIMT-), and the frequencies of anti-dsDNA positivity for 7 years, were evaluated. Serum inflammatory and oxidative stress biomolecules, and NETosis-derived bioproducts were further evaluated by multiplex assay and specific commercial kits, respectively. Besides, miRNnomes were identified using next-generation sequencing. Clinical significance of the biomolecules analyzed was explored by correlation/association studies with immunological and CV-risk features. Results: A significant relationship among the incidence of CVD (i.e. thrombosis or cardiac involvement) and the positivity for anti-dsDNA antibodies was recognized in the first SLE cohort. Accordingly, in the second SLE cohort, significantly impaired micro-vascular endothelial function (identified by reduction of hyperemia post-occlusion area), increased atherogenic index and pathologic increase in the CIMT were assessed in patients positive for anti-dsDNA in relation to anti-dsDNA negative patients. Around a 65% of SLE patients displayed a sustained positivity for anti-dsDNA antibodies for more than 7 years. These patients showed a distinctive and specific molecular profile compared with patients that had remained negative for anti-dsDNA, including increased inflammatory profile (IL1B, IL2, IL6, IL17, EOTAXIN, FGF, GMCSF, IFNγ, IP10, RANTES, TNF), enhanced oxidative status (lipoperoxides), and higher NETosis (nucleosomes, elastase). Levels of those biomolecules were closely interconnected and associated to their regulatory miRNAs, which accordingly exhibited differential expression in SLE anti-dsDNA(+) vs anti-dsDNA(-) patients. Finally, the frequency for positivity of anti-dsDNA significantly correlated both with markers of endothelial dysfunction and with the presence of atheroma plaques in SLE patients, pointing at the direct involvement of anti-dsDNA-Abs in the development of these processes. Conclusion: 1. Positivity for anti-dsDNA antibodies confers a specific molecular profile linked to an enhanced CV-risk in SLE patients. 2. Moreover, the sustained positivity for anti-dsDNA antibodies fosters the establishment of an atherothrombotic status in these autoimmune patients. Acknowledgments: Supported by the EU/EFPIA –IMI-JU PRECISESADS (n° 115565) and ISCIII (PI18/0837 and RIER RD16/0012/0015), Co-funded with FEDER. Disclosure of Interests: Alejandra M. Patiño-Trives: None declared, Maria A Aguirre: None declared, Carlos Pérez Sánchez: None declared, Pérez Sánchez Laura: None declared, María Luque-Tévar: None declared, Iván Arias de la Rosa: None declared, Rafaela Ortega Castro: None declared, Maria del Carmen Abalos-Aguilera: None declared, Mario Espinosa: None declared, Pedro Seguí Azpilcueta: None declared, Jacques-Olivier Pers: None declared, Nuria Barbarroja Puerto Grant/research support from: ROCHE and Pfizer., Speakers bureau: ROCHE and Celgene., Marta Alarcon-Riquelme: None declared, Eduardo Collantes Estevez Grant/research support from: ROCHE and Pfizer, Speakers bureau: ROCHE, Lilly, Bristol and Celgene, Chary Lopez-Pedrera Grant/research support from: ROCHE and Pfizer.